2017
DOI: 10.1111/jcpp.12728
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of a parent‐mediated intervention for infants at high risk for autism: longitudinal outcomes to age 3 years

Abstract: BackgroundThere has been increasing interest in the potential for pre‐emptive interventions in the prodrome of autism, but little investigation as to their effect.MethodsA two‐site, two‐arm assessor‐blinded randomised controlled trial (RCT) of a 12‐session parent‐mediated social communication intervention delivered between 9 and 14 months of age (Intervention in the British Autism Study of Infant Siblings‐Video Interaction for Promoting Positive Parenting), against no intervention. Fifty‐four infants (28 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
223
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(242 citation statements)
references
References 39 publications
7
223
0
4
Order By: Relevance
“…The gains in language, social, play, cognitive, and adaptive functioning, sometimes substantial, associated with some interventions, is very encouraging, and can have sustained effects (e.g. Green et al, 2017; Landa & Kalb, 2012). However, identification of positive treatment effects in the literature does not imply that EI should be limited to the early childhood period.…”
Section: Interpreting the Results Of Early Intervention Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The gains in language, social, play, cognitive, and adaptive functioning, sometimes substantial, associated with some interventions, is very encouraging, and can have sustained effects (e.g. Green et al, 2017; Landa & Kalb, 2012). However, identification of positive treatment effects in the literature does not imply that EI should be limited to the early childhood period.…”
Section: Interpreting the Results Of Early Intervention Studiesmentioning
confidence: 99%
“…Non-significant negative treatment effects were identified for child receptive language and P100 in an evoked response potential task. Infant follow-up at 1- and 2-years (Green et al, 2017) identified beneficial treatment effects on reduced severity of ASD symptoms and increased levels of child social engagement with parents in the VIPP group, from baseline to 39 months of age. The negative treatment effects identified in the VIPP group at the end of the intervention period were not sustained; there were no group differences in language performance at either follow-up visit.…”
Section: Naturalistic Developmental Behavioural Intervention (Ndbi) Amentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, advances in the understanding and early identification of ASD promoted a shift from reactive to preventative efforts in the treatment of core ASD symptoms [30, 88, 89]. This approach capitalizes on the opportunity to target symptoms of ASD during early sensitive periods when neurodevelopmental trajectories can be advantageously altered [90].…”
Section: Resultsmentioning
confidence: 99%
“…The final assessment was the longitudinal outcomes up to the age of 3 years. They recruited a high-risk group of infants with a familial risk of autism 6 . This very first randomized controlled trial of a very early social communication intervention for infants at familial risk of developing autism and followed up for 3 years has shown a treatment effect, extending to 24 months after the intervention ended, to reduce the overall severity of autism prodromal symptoms and enhance parent-child social communication over this period.…”
mentioning
confidence: 99%